The role of ABC transporter DrrABC in the export of PDIM in Mycobacterium tuberculosis - Nabiela Moolla; Helen Weaver; Rebeca Bailo; Albel Singh; Vassiliy N. Bavro; Apoorva Bhatt (The Cell Surface)
The Mycobacterium tuberculosis virulence lipid phthiocerol dimycocerosate (PDIM) is exported by a complex mechanism that involves multiple proteins including the Resistance-Nodulation-Division (RND) transporter MmpL7 and the lipoprotein LppX. Here, we probe the role of the putative heterooligomeric ATP-Binding Cassette (ABC) transporter complex composed of DrrA, DrrB and DrrC in PDIM transport by constructing a set of individual null mutants of drrA, drrB and drrC in the vaccine strain Mycobacterium bovis BCG. Loss of all three, or individual drr genes, all resulted in a complete loss of PDIM export to the outer envelope of the mycobacterial cell. Furthermore, guided by a bioinformatic analysis we interrogated specific signature residues within the DrrABC to demonstrate that it is indeed an ABC transporter, and our modelling, together with the mutagenesis identify it as a member of the Type V family of ABC exporters. We identify several unique structural elements of the transporter, including a non-canonical C-terminally inserted domain (CTD) structure within DrrA, which may account for its functional properties.